2021
DOI: 10.23937/2474-1353/1510130
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude and Practice of Contraceptive Use among Postpartum Women in Jimma University Medical Center, Jimma Town, South West Ethiopia

Abstract: Background: Population growth remains high in the group of 48 countries designated by the United Nations as the least developed countries (LDCs), of which 27 are in Africa. Ethiopia, the second most populous country in Africa, still has high fertility rate (4.6 children per woman) and fast population growth rate. Despite the enormous benefits of using modern contraceptive methods, the utilization of contraceptives remains low in Sub-Saharan Africa including Ethiopia. Many women in the postpartum period do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…In the current study, all married respondents were able to name more than one method of contraception and had used or were using at least one contraceptive method. Twenty-two (22) out of the 32 participants (1/3) had a considerably good knowledge of methods of contraception which is consistent with the findings of a study in Ethiopia [ 30 ]. Studies elsewhere have reported low levels of knowledge of modern contraceptives among women [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 83%
“…In the current study, all married respondents were able to name more than one method of contraception and had used or were using at least one contraceptive method. Twenty-two (22) out of the 32 participants (1/3) had a considerably good knowledge of methods of contraception which is consistent with the findings of a study in Ethiopia [ 30 ]. Studies elsewhere have reported low levels of knowledge of modern contraceptives among women [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 83%
“…In the current study, all married respondents were able to name more than one method of contraception and had used or were using at least one contraceptive method. Twenty-two ( 22) out of the 32 participants (1/3) had a considerably good knowledge of methods of contraception which is consistent with the ndings of a study in Ethiopia [30]. Contrary, low levels of knowledge on modern contraceptives among women have been reported elsewhere [31,32].…”
Section: Discussionsupporting
confidence: 79%
“…The development of technology gives a challenge for the Z generation, internet connection, social media, free life, staying away from their parents, and liberty from the familiarized community, this group is categorized as a risky population and has to engage in risky sexual behavior and have a poor sense of vulnerability [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%